Pola Aktivitas di Kebun Raya ITERA untuk Meningkatkan Kebahagiaan Masyarakat - Mahmudi, Naswa Asyfa; Pratiwi, Dita Asri; Sitompul, Rabita Akbari (Jurnal Teknik dan Teknologi Indonesia, 2025)
The rapid urban development in Bandar Lampung has led to significant reductions in Green Open Spaces (RTH), contributing to environmental issues and diminished public well-being. ITERA Botanical Gardens (Kebun Raya ITERA) presents an opportunity to address these concerns by serving as a multifunctional green space for conservation, education, and recreation. This study aims to explore the activity patterns of visitors to Kebun Raya ITERA and their impact on enhancing community happiness and emotional well-being. Employing qualitative descriptive methods, data were collected through field observations, interviews, and literature reviews, focusing on visitor interactions with green spaces and their perceived benefits. Results indicate that activities such as passive recreation, active sports, educational pursuits, and social interactions significantly contribute to reducing stress and improving psychological health. Recommendations include enhancing facilities, accessibility, and educational initiatives to maximize the garden's potential as a sustainable urban green space. This research highlights the critical role of green open spaces in fostering community happiness, contributing to both individual well-being and broader societal benefits.